2015
DOI: 10.1111/1471-3802.12116
|View full text |Cite
|
Sign up to set email alerts
|

Preparing preschool teacher candidates for inclusion: impact of two special education courses on their perspectives

Abstract: Successful implementation of inclusive practices depends mainly on teachers' attitudes towards children with special needs and their inclusion, and teachers' willingness to work with children with special needs in their classrooms. Experiences teacher candidates have during pre‐service stage might influence their perceptions towards children with disabilities and their inclusion. The purpose of this study was to examine the impact of two special education courses on (1) preschool teacher candidates' general at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
1
19
0
10
Order By: Relevance
“…What is critical, however, is the transfer of this knowledge into classroom practice. Research evidence suggests that instruction on EBPs in a university course alone is not sufficient to promote preservice teachers use of these practices in their classrooms (Coogle et al, 2015; Hemmeter, Snyder, Kinder, & Artman, 2011) and that field experiences coupled with coursework have a stronger effect on preservice teachers’ practices than college coursework alone (Barton et al, 2013; Leko, Brownell, Sindelar, & Kiely, 2015; Rakap, Cig, & Parlak-Rakap, 2015; Scheeler et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…What is critical, however, is the transfer of this knowledge into classroom practice. Research evidence suggests that instruction on EBPs in a university course alone is not sufficient to promote preservice teachers use of these practices in their classrooms (Coogle et al, 2015; Hemmeter, Snyder, Kinder, & Artman, 2011) and that field experiences coupled with coursework have a stronger effect on preservice teachers’ practices than college coursework alone (Barton et al, 2013; Leko, Brownell, Sindelar, & Kiely, 2015; Rakap, Cig, & Parlak-Rakap, 2015; Scheeler et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Lack of training on educating children with disabilities and those who have severe behaviour problems increases the negative attitudes towards inclusion of these children. Rakap, Cig, and Parlak-Rakap (2015) reported that pre-service teachers' attitudes towards inclusion of young children with severe behaviour problems positively changed only after they took a course focused on supporting social-emotional development and addressing challenging behaviours of young children with disabilities. Rakap, Cig, and Parlak-Rakap (2015) also found that an introductory course on special education was not effective for positively changing pre-service teachers' attitudes towards inclusion of young children with physical, cognitive, or behavioural disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers reported that pre-service teachers have favourable attitudes and support towards inclusion of children with disabilities into regular education classrooms (Avramidis, Bayliss, and Burden 2000;Beacham and Rouse 2012;Park, Chitiyo, and Choi 2010;Rakap, Cig, and Parlak-Rakap. 2015;Ryan 2009;Sharma and Sokal 2013), while others reported more negative pre-service teacher attitudes (Hastings and Oakford 2003;Kayili et al 2010;Orel, Zerey, and Toret 2004;Sahbaz and Kalay 2010).…”
Section: Literature On In-service and Pre-service Teacher Attitudes Tmentioning
confidence: 99%
“…The group of scientists S. Rakap et al (2017) researched the influence of special education courses on the following indicators: general relation of teachers to students with special needs; readiness of pedagogues for work with students with intellectual, physical and behavioural disorders. The authors have concluded that successful implementation of inclusive practice depends on the attitude of teachers to students with special needs, and their readiness to work with students with limited health opportunities.…”
Section: The Analysis Of Foreign Researchmentioning
confidence: 99%